2006
DOI: 10.1002/malq.200510016
|View full text |Cite
|
Sign up to set email alerts
|

On Löb algebras

Abstract: We study the variety of Löb algebras, the algebraic structures associated with formal propositional calculus. Among other things, we prove a completeness theorem for formal propositional logic with respect to the variety of Löb algebras. We show that the variety of Löb algebras has the weak amalgamation property. Some interesting subclasses of the variety of Löb algebras, e. g. linear, faithful and strongly linear Löb algebras are introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…These algebras are the natural algebraic models for sub-intuitionistic logics. See for instance [39], [19], [15], [5], [6], [7] and [8] for the algebraic notions and [12], [13], [9] and [39] for their role in sub-intuitionistic logics.…”
Section: Abstract Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These algebras are the natural algebraic models for sub-intuitionistic logics. See for instance [39], [19], [15], [5], [6], [7] and [8] for the algebraic notions and [12], [13], [9] and [39] for their role in sub-intuitionistic logics.…”
Section: Abstract Implicationsmentioning
confidence: 99%
“…This implication is morally the Heyting implication without its modus ponens rule; see [12], [14], [13], [18]. The emergence of these weak implications then set the scene for a plethora of other and sometimes even weaker implications emerging philosophically [43]; algebraically [39], [19], [5], [6], [7], [8], [9], [15]; proof theoretically [20], [21], [48], [45]; arithmetically [52], [23], [24] and via relational semantics [11], [30], almost everywhere in the logical realm. Apart from the philosophically oriented reasons, the weak implications raise also some independent mathematical interests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The counterpart logic of this algebra, also called Basic Logic, was first introduced by Visser [19] in 1981 and investigated further by Ruitenberg [14] in 1992. In 2006, Alizadeh and Ardeshir [2] studied Löb algebras, which are a subset of the Basic algebra, and proved the completeness of the counterpart logic of this algebra. They introduced countably many locally finite subvarieties of the variety of Löb algebras and showed that their corresponding intermediate logics have the interpolation property (cf.…”
Section: Introductionmentioning
confidence: 99%